Dilemmas of human potential management, from the viewpoint of employment security = Dylematy gospodarowania potencjałem ludzkim z perspektywy bezpieczeństwa zatrudnienia - Bodak, Andrzej; Cierniak-Emerych, Anna; Gableta, Małgorzata; Pietroń-Pyszczek, Agata; Piwowar-Sulej, Katarzyna (Zielona Góra: Faculty of Economics and Management Press)
In this study - based on the result of own and others empirical research, regarding conditions of person?s functioning in the process of work during the last decade of 2000?s - an attempt of indicating dilemmas connected with shaping of employment security has been made.
Keywords: elastyczność; formy zatrudnienia; zmiany pokoleniowe; zarządzanie projektami; flexibility; form of employment; generational changes; project management